Analysis of the condition of forest interior and edge in Mount Papandayan, West Java, Indonesia based on floristic composition and structural characteristics of tree community - ENDAH SULISTYAWATI; EKA FATMAWATI TIHURUA (Society for Indonesian Biodiversity, 2019)
Abstract. Sulistyawati E, Tihurua EF. 2019. Analysis of the condition of forest interior and edge in Mount Papandayan, West Java, Indonesia based on floristic composition and structural characteristics of tree community. Biodiversitas 20:  900-906.  Forest fragmentation creates forest edges that possess different biotic characteristic in comparison to its interior. Those differences may include difference in vegetation structure and composition, and ecological processes in the ecosystem. This study aims to compare the condition between forest interior and forest edge in Mount Papandayan and provide assessment of the overall condition of the forest based on its floristic and structural characteristics. We conducted vegetation analysis of tree in which six plots, each of 0.1 ha, were established in the forest interior and forest edge. Based on the results, species richness and diversity of tree were higher in the forest interior than the forest edge. Based on the importance value index, the proportion of co-dominant species in forest edge sites were higher than in the forest interior sites. In addition, tree density, regeneration potential, total basal area, wood density average, and biomass were higher in the forest interior than in the forest edge. Overall, Mount Papandayan suffers moderate disturbance, which follows through the intermediate disturbance hypothesis and this can be seen from its relatively high diversity index of tree yet it has moderate wood density average.